Effects of inclined baffle location and Prandtl number on natural convection in a cavity - Ozgen, F.; Varol, Y.; Öztop, Hakan Fehmi (My University, 2014)
The problem of steady, laminar, conjugate-natural convection in a square cavity with an adiabatic baffle mounted on a vertical wall at different positions is formulated. In this study, natural convection heat transfer in a square cavity with an adiabatic fin mounted on a vertical wall was investigated numerically. Navier-Stokes equations have been performed and they are solved using finite difference method (FDM). Results are obtained for various parameters as the baffle location (0.25 ? h ? 0.75), thickness (t=0.033), length of baffle (0.25 ?w? 0.75), Rayleigh numbers (103 ? Ra ? 106). Prandtl number values are Pr=0.7, 1 and 7, is investigated. Results were presented with streamlines, isotherms, local and mean Nusselt numbers. It was found that Prandtl number and presence of the baffle on the wall have significant effect on natural convection.

Bu çalışmada, düşey duvarına farklı pozisyonlarda adyabatik engel yerleştirilmiş kare bir hacimdeki laminar doğal taşınım ısı transferi formüle edilmiştir. Düşey duvarında engel bulunan kapalı hacimdeki ısı transferi nümerik olarak da incelenmiştir. Navier-Stokes denklemleri kullanılmış ve denklemler sonlu farklar metodu (FDM) ile çözülmüştür. Sonuçlar, engelin farklı yerleşimi (0.25 ? h ? 0.75), farklı kalınlığı (t=0.033), farklı uzunluğu (0.25 ?w? 0.75) ve Rayleigh sayıları için (103 ? Ra ? 106) sunulmuştur. Prandtl sayısı değeri 0.7, 1 ve 7 alınmıştır. Sonuçlar, akım çizgileri, sıcaklık profilleri, yerel ve ortalama Nusselt sayıları şeklinde gösterilmiştir. Prandtl sayısı ve engelin duvar üzerindeki konumunun, doğal taşınımı önemli derecede etkilediği görülmüştür.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Natural convection; Square enclosure; Inclined baffle; Fin; Doğal taşınım; Kare hacim; Eğimli engel; Plaka